Early Warning Systems (E-Wars) Design for Early Detection of Stroke Incidence - Erawantini, Feby; Karimah, Rinda Nurul (Folia Medica Indonesiana, 2018)
Stroke is a neurological disease whose occurrence increases from year to year and causes disability and death worldwide. Stroke is caused by many factors or multicausal. This was a qualitative study conducted for one year with system design using prototype method. The prototype method began with the identification of needs, mapping, and then inference mechanism. Identification of needs was based on the literature review and discussion. The literature review from 15 sources consisting of journal articles, books and proceedings was done by comparing, contrasting, criticizing, synthesizing and summarizing. Stroke risk factor discussion were carried out with neurologists. The results of the review and literature discussion found identification of factors that cause stroke, which consisted of hypertension, high blood glucose, cholesterol, heart disease, behavioral factors, such as smoking behavior and alcoholism, stress and other causes. The risk factors of stroke were then mapped in the form of mobile application prototype through inference mechanism. The output in this study was early warning systems (E-WARS) prototype for early detection of stroke occurrence. The prototype results were expected to be used in operations into mobile applications that were beneficial to the public, in particular for self-control and personal risk factors for stroke. It was intended for early screening and early detection of the risk of stroke.